Environmental Crisis and Mobility in Oases Societies of Morocco: The Cases of Imilchil and Merzouga - Lacomba, Joan; Berlanga Adell, María Jesús (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2026)
The oases of Morocco have undergone profound socio-environmental transformations in recent decades that have affected their ways of life and their economies, impacting especially the culture of nomadism and increasing the weight of other forms of mobility such as tourism and migration. To address these changes, this article adopts an ethnographic approach, employing fieldwork and using observation and interviews as its primary techniques. The towns of Imilchil (a mountain oasis in the Eastern High Atlas) and Merzouga (a desert oasis in the Ziz Valley) were selected for study based on their shared nomadic past and the increasing presence of tourism and migration. The research findings demonstrate how the combination of new and old forms of mobility and immobility forms part of attempts to adapt to changing environmental and climatic conditions, as well as part of the essential role of the state and its policies.